2015
DOI: 10.3109/13880209.2015.1063673
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect on phenytoin-induced cognition deficit in pentylenetetrazol kindled mice: A repertoire ofGlycyrrhiza glabraflavonoid antioxidants

Abstract: From the results, it can be concluded that the flavonoid rich fraction in combination with phenytoin reduces seizure severity and improve cognitive functions in PTZ-kindled mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“… 43 In addition, G glabra reduced nitrogen radicals and enhanced mitochondrial function during cellular metabolism abating the initial production of free radicals. 20 , 44 Because of its ability to lower ROS, G glabra can decrease the total level of oxidative stress, which indirectly impedes cortisol release . Therefore, although G glabra has been shown to increase the release of cortisol, which is an immunosuppressant, and only has weak cortisol modulatory activity, the anti-inflammatory and antioxidant potential of G glabra may hinder cortisol release, lessening the immunosuppressive effect of cortisol.…”
Section: Discussionmentioning
confidence: 99%
“… 43 In addition, G glabra reduced nitrogen radicals and enhanced mitochondrial function during cellular metabolism abating the initial production of free radicals. 20 , 44 Because of its ability to lower ROS, G glabra can decrease the total level of oxidative stress, which indirectly impedes cortisol release . Therefore, although G glabra has been shown to increase the release of cortisol, which is an immunosuppressant, and only has weak cortisol modulatory activity, the anti-inflammatory and antioxidant potential of G glabra may hinder cortisol release, lessening the immunosuppressive effect of cortisol.…”
Section: Discussionmentioning
confidence: 99%
“…D. spatulata contain several flavonoids 28 and it has been reported that flavonoids have antioxidant properties 8,29,30 . Therefore it seems that these compounds have some role in the analgesic effect.…”
Section: Discussionmentioning
confidence: 99%
“…The mice were then placed into a cage and behavior was observed. Seizures were scored according to a modified Racine scale (Racine, 1972;Lüttjohann et al, 2009;Singh et al, 2016) with the following scores: 1 -sudden behavioral arrest; 2 -facial jerking; 3 -myoclonic jerks; 4 -clonic seizure, sitting; 5 -clonic, tonic-clonic seizure, lying on belly; 6, clonic, tonic-clonic seizure with loss of posture and wild jumping; with notation of time of onset of each intensity of seizure and tallying of maximal seizure intensity in two-minute bins. Seizure behavior typically subsides by thirty minutes after PTZ administration, so animals were then returned to their home cages.…”
Section: Behavioral Studymentioning
confidence: 99%